Peternakan Ayam Jawa Super Delima Kedaton (Dengan Lima Profit Keuntungan dan Toko Online) - Haryono, Haryono; Pambudhi, Radna; Chanifia, Muna (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
According to Director Generalof Livestock Production currently supply new chicken meat can meet 5.5% of total national chicken meat needs. In the next 10 years is expected chicken supplies will reach 25% of the total national chicken meat needs. In fact farming chicken encountered major obstacles that growth tends to be slower when compared to the broiler capable harvest in 40 days. The selling price of chicken is super higher than broiler chicken, super chicken is across between chicken java (male) with chicken arabic (female). This type of chicken called chicken because chicken has a super character, nature and taste the same as the original chicken, but still has some other advantages, namely: shorter maintenance period (between 4-5 months) with an average weight of 0.7-1kg (weight demanded by consumer seating house/restaurant), way easier maintenance and more resistant to isease (small mortality), Impurities in cages odorless, easy marketing, profitable (profitable). prices range from Rp. 50.000-Rp. 70,000/kg according to market research during the year 2013 while the widths/big day can reach Rp.80.000-100,000 /kg. The method implementation is done in several phases: Phase I Preparation (selection and crossover market surveys), Phase Implementation (hatching, rearing), Packaging Phase III, Phase IV Phase V Evaluation Sales and calculations, Phase VI Reporting. Marketing strategies used to increase sales, among others, with the distribution of leaflets, posters and attractive packaging Eggs sold at whole Rp. 1500-@ Rp. 2000 to. Chicken forth meal (roast chicken) aged 4-6 months @Rp. 45,000. Stool sare sold in the form of fertilizer per kg@Rp.6.500. From the analysis of the work done, got a profit of Rp1,536,750a month, the value of B/C ratio of 2.6 and the value obtained Payback Period (PBP) or there turn of capital for 18 days. Poultry business then Java Super DELIMAKEDATON (With Five Advantages and Stores On Line) is feasible to be developed and maybe a promising business opportunity profits. Keywords : Chickenjavasuper, DOC(Day OldChick), business opportunities